2022
DOI: 10.3389/fphar.2022.869488
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitors in Peripheral T-Cell Lymphoma

Abstract: Peripheral T-cell lymphomas (PTCLs) are highly heterogeneous and present significant treatment challenges. Immune checkpoint therapies, such as PD-1 and CTLA-4 inhibitors, have significantly changed the clinical management paradigm of tumors. The roles of immune checkpoints in PTCL and related agents have been actively explored over recent years. PD-1 and PD-L1 expression is detectable in both PTCL and immune cells within the tumor microenvironment and forms the basis for the exploration of antibodies targetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 124 publications
0
12
0
Order By: Relevance
“…Two prerequisites for this strategy are (i) the sufficient availability of residual healthy T cells and (ii) the independence of lymphoma cell growth from checkpoint-mediated signaling, a particular pitfall when targeting T cell lymphomas using T cell reactivators. Two important immune-checkpoint signals that regulate T cell activity, and that can be targeted for anti-cancer therapies, are PD-1-PDL-1 and CTLA-4-CD80/CD86 interactions [21,92].…”
Section: Antibodies As Immune-checkpoint Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two prerequisites for this strategy are (i) the sufficient availability of residual healthy T cells and (ii) the independence of lymphoma cell growth from checkpoint-mediated signaling, a particular pitfall when targeting T cell lymphomas using T cell reactivators. Two important immune-checkpoint signals that regulate T cell activity, and that can be targeted for anti-cancer therapies, are PD-1-PDL-1 and CTLA-4-CD80/CD86 interactions [21,92].…”
Section: Antibodies As Immune-checkpoint Inhibitorsmentioning
confidence: 99%
“…Notably, only three immune system-based therapies have ever achieved approval by drug administration agencies for the treatment of only a small subgroup of MTCL/L, with only two remaining FDA approved medications to date: the anti-CD30 antibodydrug conjugate Brentuximab vedotin (ALCL and CD30 + CTCL; first-line in 2018) [17]; the anti-CD52 antibody Alemtuzumab (originally for B-cell CLL in 2007, withdrawal from market for oncologic applications in 2012) [13,18], and the anti-CCR4-receptor antibody Mogamulizumab for SS and MF (second-line in 2018), as well as CCR4 + ATLL (in Japan 2018) [19,20]. In the case of relapsed/refractory (r/r) disease, only a few targeted substances are approved (e.g., the histone deacetylase (HDAC) inhibitor Belinostat), showing unsatisfactory responses [21].…”
Section: Introductionmentioning
confidence: 99%
“…CTLA-4 inhibitors thus function by inhibiting CTLA-4, allowing CD28-B7 crosslinking and activation of T cells for its activity against tumor cells. A study of PTCL via Sanger sequencing identified that CTLA-4/CD28 fusion genes occurred in approximately 30% of PTCL samples, and up to 58% in AITL ( 128 ). Despite the similarities that it shares with the PD-1/PD-L1 pathways, CTLA-4 inhibitors have not yet been adequately studied in the population of PTCL within clinical trials despite there being pharmacological agents such as ipilimumab available in the market for the treatment of other malignancies ( 128 ).…”
Section: Emerging Therapeutic Strategiesmentioning
confidence: 99%
“…A study of PTCL via Sanger sequencing identified that CTLA-4/CD28 fusion genes occurred in approximately 30% of PTCL samples, and up to 58% in AITL ( 128 ). Despite the similarities that it shares with the PD-1/PD-L1 pathways, CTLA-4 inhibitors have not yet been adequately studied in the population of PTCL within clinical trials despite there being pharmacological agents such as ipilimumab available in the market for the treatment of other malignancies ( 128 ). However, a case series performed on PTCL tumors had found substantial CTLA-4 mutations in various subtypes of PTCL, notably in that of AITL and PTCL-NOS, suggesting possible room for therapeutics against the CTLA-4 surface marker in future studies ( 129 ).…”
Section: Emerging Therapeutic Strategiesmentioning
confidence: 99%
“…Current ICB activates tumor-reactive T cells by downregulating the inhibitory signaling pathway or overcoming regulatory mechanisms that prevent T cell activation (26). Promising immune targets of ICB that focus on PD-1 and cytotoxic T-lymphocyte-associated protein 4 (CTLA-4), are summarized in Figure 1 (26)(27)(28)(29). These immune checkpoints are primarily located on the surface of T cells, natural killer (NK) cells, dendritic cells (DCs), B cells, monocytes, macrophages, and neutrophils (30).…”
Section: The Rationale and Study Status Of Icbmentioning
confidence: 99%